Membros: v. 18, n. 2 (2020) - ., . (RENOTE, 2021)
Comitê Técnico Adilson Vahldick - Universidade do Estado de Santa Catarina Adriano Teixeira - Universidade de Passo Fundo Alex Mazzuco - Universidade Federal do Rio Grande do Sul (UFRGS) Alexandra Lorandi Macedo - Universidade Federal do Rio Grande do Sul Aliane Krassmann - Instituto Federal Farroupilha (IFFar); Universidade Federal do Rio Grande do Sul (UFRGS) Ana Marli Bulegon - Universidade Franciscana (UFN) André Peres - IFRS - Campus Porto Alegre Andre Zanki Cordenonsi - Universidade Federal de Santa Maria Andreia Solange Bos - UFRGS- Universidade Federal Rio Grande do Sul Barbara Avila - Instituto Federal farroupilha Breno Fabrício Terra Azevedo - IFF Carine Loureiro - Instituto Federal Rio Grande do Sul Carla Barvinski - Universidade Federal da Grande Dourados Carla Berkenbrock - Universidade do Estado de Santa Catarina - UDESC Cícero Quarto - UEMA Cecilia Flores - Universidade Federal de Ciências da Saúde de Porto Alegre Cristina Martins - Pontifícia Universidade Católica do Rio Grande do Sul Cristina Mesquita - Polytechnic Institute of Bragança Cristina Pescador - Universidade de Caxias do Sul Daniel Lopes - Universidade Federal do Rio Grande do Sul Daniela Bagatini - Universidade Federal do Rio Grande do Sul (UFRGS)/Universidade de Santa Cruz do Sul (UNISC) Débora Valletta - Universidade Federal do Rio Grande do Sul Débora da Silva Soares - Universidade Federal do Rio Grande do Sul Ederson Bastiani - Instituto Federal Farroupilha - Campus Panambi Elisa Boff - Universidade de Caxias do Sul Elisa Friedrich Martins - UFRGS Eliseo Reategui - Universidade Federal do Rio Grande do Sul Emanuel Queiroga - Universidade Federal de Pelotas Erico Amaral - Universidade Federal do Pampa - Unipampa Evandro Preuss - Universidade Federal do Rio Grande do Sul Fabiana Sgobbi - Universidade Federal do Rio Grande do Sul Fabrício Herpich - Universidade Federal do Rio Grande do Sul (UFRGS) Felipe Becker Nunes - Antonio Meneghetti Faculdade Francieli Ludovico - Universidade Federal do Rio Grande do Sul Giliane Bernardi - Universidade federal de Santa Maria Gilse Falkembach - UFRGS Gleizer Voss - Instituto Federal Farroupilha Heli Meurer - PROCERGS - Centro de Tecnologia da Informação e Comunicação do Estado do Rio Grande do Sul S.A. Herik Rodrigues - Universidade Estadual do Piauí Janete Sander Costa - Universidade Federal do Rio Grande do Sul juarez bento Silva - Universidade Federal de Santa Catarina Juliano Varella de Carvalho - Universidade Feevale Karen Cardoso - UFRGS Kátia Rocha - Universidade Federal do Rio Grande do Sul Ketia Kellen da Silva - NUTED/UFRGS Larissa Monzon - UFRGS Leticia Machado - Universidade Federal do Rio Grande do Sul Liane Margarida Rockenbach Tarouco - UFRGS Lucia Giraffa - PUC-RS Maira Bernardi - Universidade Federal do Rio Grande do Sul Manuel Zunguze - Universidade Pedagógica de Maputo Marcelo Foohs - Universidade Federal do Rio Grande do Sul Marcelo Motta - Universidade Tecnológica Federal do Paraná Marcelo Schmitt - Instituto Federal do Rio Grande do Sul - Campus Porto Alegre Marcia Notare - UFRGS Marcio Bigolin - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS) - Campus Canoas Marco Trentin - UPF Marcus Basso - UFRGS Maria Lydia Fioravanti - ICMC-USP Mariana Backes Nunes - UFRGS Marilda Spindola - Universidade de Caxias do Sul Marlise Geller - Universidade Luterana do Brasil Márcia de Borba Campos - Faculdade Inedi - CESUCA Míria Santanna dos Santos - UFRGS Melissa Meier - Universidade Federal do Rio Grande do Sul Patrícia B. Scherer Bassani - Universidade Feevale Patrícia Campelo Costa Barcellos - Universidade Federal do Rio Grande do Sul Patrícia F. da Silva - Universidade Federal do Rio Grande do Sul Patricia Alejandra Behar - Universidade Federal do Rio Grande do Sul Patricia Estivalete - Universidade Federal do Rio Grande do Sul Pedro Henrique Dias Valle - Universidade de São Paulo Priscila Nicolete - Universidade Federal do Rio Grande do Sul Querte Mehlecke - Universidade Federal do Rio Grande do SUl - PGIE; Faculdade QI; Faculdades de Taquara-FACCAT/RS Ricardo Radaelli - UFSM Rodrigo de Oliveira Soares - Universidade Federal do Rio Grande do Sul Rodrigo Machado - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul Rodrigo Silva - UFRGS, DMPA (Departamento de Matemática Pura e Aplicada) Rosa Viccari - UFRGS Rosane Aragón - UFRGS Roseclea Medina - Universidade Federal de Santa Maria Rui Lopes - Polytechnic Institute of Braganca Sandra Assumpção Maria - UFRGS - Universidade Federal do Rio Grande do Sul Sílvio Cazella - UFCSPA Silvia Bertagnolli - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul Simone Oliveira - Universidade Federal do Rio Grande do Sul Taciana Pontual Falcão - Universidade Federal Rural de Pernambuco Taiser Barros - PPGIE UFRGS Tiago Oliveira - Federal University at Sao Paulo - UNIFESP Valéria Costa - Fundação Oswaldo Cruz Vandoir Stormowski - UFRGS - Universidade Federal do Rio Grande do Sul Vinicius Hartmann Ferreira - IFRS - Campus Feliz Viviane Backendorf - UFRGS Coordenação Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - UFRGS